2011
DOI: 10.1097/prs.0b013e31820a6511
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acellular Dermal Matrix in Release of Burn Contracture Scars in the Hand

Abstract: Acellular dermal matrix can be an effective tool in surgical treatment of difficult burn contracture deformity in the hand, with lasting results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…[6][7][8] However, because it only functionally serves to replace the dermal layer, epidermal coverage in the form of a split-thickness skin graft is still needed. Regardless, numerous studies have demonstrated that the addition of acellular dermal matrix use in this setting results in a faster healing time, 9,10 better aesthetic outcome with improved skin elasticity, and reduced scar contracture [11][12][13][14][15][16][17][18][19] ; can serve as a temporizing measure to avert the need for emergency surgery 19 ; and allows improved mobility and function of joints that require skin coverage.…”
Section: Basic Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] However, because it only functionally serves to replace the dermal layer, epidermal coverage in the form of a split-thickness skin graft is still needed. Regardless, numerous studies have demonstrated that the addition of acellular dermal matrix use in this setting results in a faster healing time, 9,10 better aesthetic outcome with improved skin elasticity, and reduced scar contracture [11][12][13][14][15][16][17][18][19] ; can serve as a temporizing measure to avert the need for emergency surgery 19 ; and allows improved mobility and function of joints that require skin coverage.…”
Section: Basic Sciencementioning
confidence: 99%
“…10,[12][13][14]18 Although there are clear benefits to its use, acellular dermal matrix will never serve as a complete replacement for autologous tissue transfer in this setting, and more prospective data are needed (Table 2). 6, Certain techniques, such as meshing of skin substitutes combined with negative-pressure wound therapy, have improved take of these grafts and ensured improved outcomes. The products in Table 3 address acellular dermal matrix types that are used for other diverse soft-tissue applications that include, but are not limited to, abdominal and thoracic wall reconstructions, breast reconstructions, and hernia repair.…”
Section: Basic Sciencementioning
confidence: 99%
“…Die Wahl der Methode ist abhängig von der Defektgröße und der Menge des noch vorhanden gesunden Gewebes. Die einfachste aller Möglichkeiten ist die Deckung mit einer dermalen Matrix kombiniert mit einem Hauttransplantat [56].…”
Section: Management Von Handdeformitätenunclassified
“…42 Askari et al described their two-stage technique with ADM in nine patients undergoing release of burn contractures of the hand. 43 Following full soft tissue contracture release, including tenolysis and joint capsulotomy where indicated, meshed AlloDerm (0.50-1.05 mm thick) was…”
Section: Reconstructionmentioning
confidence: 99%